Analisa Rasio Keuangan untuk Menilai Kinerja Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2008-2011 - Eka Cahya Rizki; Harlen dro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Industry is one of sector that has an important role in the growth of a country. The development of an industry can not be separated from the industrial competition. Including the mining industry. Moreover, the mining industry is still an excellent source of income of the Indonesian. This study aims to investigate the performance of mining companies listed on the Indonesia Stock Exchange in the period 2008-2011 using financial ratio analysis and to find out which company has the better performance. Financial ratios used are liquidity ratio (CR & QR), leverage ratio (DER, LTDtER, LTDtAR, LTDtFAR, TIE), profitability ratios (ROA and ROE), and the ratio of growth (Sales & Net Income). The results showed that PT Mitra Investindo Tbk has liquidity, profitability, and growth better than Citatah Tbk PT. While in terms of leverage, Citatah Tbk PT has a better performance compared Tbk PT Mitra Investindo. Keyword : Financial Ratio, Company Performance, Liquidity Ratio, Leverage Ratio, Profitability Ratio, Growth Ratio.